Relations between spectrum curves of discrete Sturm-Liouville problem with nonlocal boundary conditions and graph theory - Vitkauskas, Jonas; Štikonas, Artūras (Lietuvos matematikos rinkinys, 2021)
Sturm-Liouville problem with nonlocal boundary conditions arises in many scientific fields such as chemistry, physics, or biology. There could be found some references to graph theory in a discrete Sturm-Liouville problem, especially in investigation of spectrum curves. In this paper, relations between discrete Sturm-Liouville problem with nonlocal boundary conditions characteristics (poles, critical points, spectrum curves) and graphs characteristics (vertices, edges and faces) were found.